2012
DOI: 10.1063/1.4730965
|View full text |Cite
|
Sign up to set email alerts
|

Three-state resistive switching in CoFe2O4/Pb(Zr0.52Ti0.48)O3/ZnO heterostructure

Abstract: The heterostructural film combining multiferroic CoFe2O4/Pb(Zr0.52Ti0.48)O3 bilayer with semiconductor ZnO layer was prepared. Three-state resistive switching was demonstrated by time-dependent current measurements under different stimuli combination of voltage pulse and magnetic bias. The asymmetry diodelike current-voltage, capacitance-voltage, and polarization-voltage loops, which seriously depend on magnetic bias, were observed. We revealed that three-state resistive switching was dominated by the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…On the other hand, when the heterostructure is under P- state, the situation is exactly opposite. W D becomes wider and more potentials drop across the depletion layer since the resistivity of the depletion layer is nearly the same as that of PZT 15 . Thereby, the switching from P+ to P− becomes harder and needs a larger applied electric field, which agrees well with the experimental results that the negative coercive electric field of ITO/PZT/ZnO/Au becomes larger than that of ITO/PZT/Au (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the heterostructure is under P- state, the situation is exactly opposite. W D becomes wider and more potentials drop across the depletion layer since the resistivity of the depletion layer is nearly the same as that of PZT 15 . Thereby, the switching from P+ to P− becomes harder and needs a larger applied electric field, which agrees well with the experimental results that the negative coercive electric field of ITO/PZT/ZnO/Au becomes larger than that of ITO/PZT/Au (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has occurred to us that if the semiconductor layer is also polarized, an extra internal field induced by this polar semiconductor might improve the PCE of the heterostructure 15 . As a typical n-type semiconductor with hexagonal wurtzite structure, ZnO not only exhibits piezoelectric (stress- or strain-induced) effect but also has a spontaneous polarization of about 4.1–7.0 μC/cm 2 16 .…”
mentioning
confidence: 99%
“…Because of the coupling at the interface between NFO and ZnO, charge status of NFO and ZnO would be changed, which results in the change of conductivity of NFO and ZnO. [23] Since NFO is also a magnetoresistance material, the total effect should be a superimposed effect of ZnO inducted charge status change and intrinsic magnetoelectric effect of NFO. That is to say, the whole sample would experience a resistivity change affected by both ferromagnetic (provided by NFO) and ferroelectric (provided by ZnO) under a changing magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al demonstrated three-state RS in films combining a multiferroic CFO/PZT bilayer with a semiconducting ZnO layer. [232] The three states are distinguished by various stimuli combinations of electric voltage pulse and magnetic bias, and are attributed to changes in the charge carrier states modulated by magnetoelectric coupling between CFO and PZT layers, as well as interface polarization coupling between PZT and ZnO layers. In an Si-SiO 2 -MgO device, the nonvolatile RS effect can be controlled by applying a magnetic field.…”
Section: Magnetic Coupled Rram Devicesmentioning
confidence: 99%